Attitude and Vibration Control of a Flexible Spacecraft Using Hybrid Adaptive Super-Twisting Non-Singular Terminal Sliding Mode Control - Valiollah Shahbahrami; Milad َAzimi; َAlireza Alikhani (فصلنامه علوم و فناوری فضایی, 2021)
In this paper, a robust adaptive hybrid control approach based on a combination of super-twisting and non-singular terminal sliding mode control (STNSMC) approaches for vibration and attitude control of a flexible spacecraft with fully coupled dynamic is developed. The proposed adaptation law eliminates the need for bounds knowledge of external disturbances and uncertainties. Then an ST-based NSMC generates a continuous control signal to reject the Chattering phenomenon, the non-singular terminal switching control law with the ability to generate continuous control commands to eliminate the chattering phenomenon. Moreover, finite-time convergence is achieved, and the singularity problem has been avoided. The overall stability of the system has been demonstrated using the Lyapunov theory. One of the essential features of the proposed control algorithm is to prevent overestimation of control gains and faster convergence rates comparing to conventional ST and non-singular terminal SMC approaches. The simulations in the form of a comparative study for large-angle maneuver reveal the advantage of the proposed approach.